Miles away from Screwing?: Queer Gothic Girlhood in John Harding's Florence and Giles. Issue 1 (1st March 2019) - Ollett, Robyn
Abstract : Literary fiction is a widely popular arena in which discourse on sexuality and queerness is produced and disseminated. The Gothic is an especially crucial mode in literary fiction that has a historically intimate relationship with queer subjectivity. Observing this relationship between Gothic fiction and queer subjectivity, in this article I analyze the representation of queer Gothic girlhood in contemporary fiction, taking as my focus John Harding's 2010 reworking of the Henry James classic, The Turn of the Screw (1898). I show how Florence and Giles develops familiar tropes attached to the figure of the queer child and look specifically at how readings of the parent text implicate contemporary readings of this figure. With close readings that draw on the queer feminist ethics of Lynne Huffer, I consider what seems to be happening to the figure of the queer Gothic girl in contemporary fiction.